How to coach individuals, teams, and organizations to master transformational change surfing tsunamis - Hacker, Stephen K. (Human resource management and organizational behavior collection, 2012)
Surfing Tsunamis gives organizational leaders, coaches, and other change agents a field-tested holistic approach for coaching and integrating transformation efforts across all levels of any organization that seeks to thrive in a radically changing world. Through transformational coaching, people learn to unleash and align the largely untapped spirit--the creative energy--in themselves, other individuals, teams, and organizations, thereby eradicating persistent performance barriers and instilling a culture where work becomes an act of co-creating a future in which everyone wins. This is the first book to present the science and art of transformational coaching across all domains--self, others, teams, and organizations-- a pragmatic yet powerful practice that has already led scores of organizations, their leaders, and their employees to achieve breakthrough results. The comprehensive approach sits at the crossroads of several leadership and management disciplines--individual and organizational development, transformational leadership, change management, organization effectiveness, employee engagement, and the growing interest in spirit in the workplace. So, be prepared to go deep and wide in this journey to embrace transformational coaching.